Virtual Vocal Learning-based Art Education - Alfa Kristanto; Muhammad Jazuli; Hartono Hartono; Udi Utomo (International Conference on Science, Education, and Technology, 2022)
The Covid-19 pandemic currently affecting the world, especially that experienced by Indonesia, has also had an impact on new adaptations in the area of education. The educational process that previously dominated, which was carried out outside the network, then in the situation of the Covid-19 pandemic, the education process switches to the network and is familiarly called online learning. With regard to the art of music, especially vocal learning, the Covid-19 pandemic situation raises creative ideas so that learning can continue effectively. One form of vocal learning during the Covid-19 pandemic is vocal learning through virtual spaces or in networks that utilize technology. This research shows that there are virtual values of art education in vocal learning. The advantages of virtual vocal learning are that a person has high expression, moral responsibility, the spirit of independence to practice can grow to the maximum, has a high enthusiasm for learning so that learning needs are not just during class, and can foster one's empathy.